The Relationship between Psychological Traits and Business (Entrepreneurial) Success: Influence of Entrepreneur’s Background - Ganga, V.; Raveeswaran, M. (Jaffna University International Research Conference, 2014)
There were several Psychological traits (Chara cteristics) those determine entrepreneurial intentions and ultimately entrepreneurial success. The problem to be discussed in this study is to determine the effect of entrepreneurial characters on entrepreneurial Success. Survey identified Psychological Variables were Need for achievement, Autonomy (need for independence), internal locus of control (Personal control), Innovation, Opportunity, Risk taking, and self-esteem of entrepreneurs. The intend of the study is to determine whether there is a relation between entrepreneurial Characteristics and entrepreneurial Success, and how an entrepreneur’s background relates to the Psychological Variables, which has been one of the arguable issue in entrepreneurship research. In this study the usable responses were 30 entrepreneurs located (Valikamam) around Thirunelvelli, University of Jaffna area, Sri Lanka; who were analyzed by using the Statistical methods. The methods of analysis include; 4 hypotheses using various statistical techniques including independent ‘t’ test and Regression. Results of the study support significant (positive) relationships between Psychological traits and entrepreneurial Success. Findings also suggest that background factors (supportive Environment) have reasonable relationships with psychological traits and entrepreneurial Success. The study also showed that there was no significant difference in the entrepreneurial success based on gender differences.
Keywords: Entrepreneur’s Background factors; Psychological Characteristics; Entrepreneurship